WASIAT DALAM PANDANGAN HUKUM ISLAM DAN BW - Nur Aisyah (El-Iqthisadi, 2019)
AbstractThe inheritance must be shared with those who have the right to receive it, in the jurisprudence there is a discussion about the science of mawaris. According to the jurists, the science of mawaris is the knowledge of knowing people who have the right to receive heirlooms, people who cannot receive heirlooms, the levels received by each inheritance and how they are distributed. Testament is one of the forms of surrender or release of property in the Islamic Shari'ah. Testament has a very strong legal basis in the Shari'ah. Testament is also called testament is "a statement of one's will regarding what will later be done on his property after he dies later". The implementation of this will will only take place after the heir has passed away.Keywords: testament, testament AbstrakHarta peninggalan, haruslah dibagi kepada orang-orang yang berhak menerimanya, di dalam fiqih terdapat pembahasan mengenai ilmu mawaris. Menurut para fuqaha, ilmu mawaris adalah ilmu untuk mengetahui orang yang berhak menerima pusaka, orang yang tidak dapat menerima pusaka, kadar yang diterima oleh tiap-tiap waris dan cara pembagiannya. Wasiat adalah satu dari bentuk-bentuk penyerahan atau pelepasan harta dalam syari'at Islam. Wasiat memiliki dasar hukum yang sangat kuat dalam syari'at. Wasiat juga di sebut testamen adalah “pernyataan kehendak seseorang mengenai apa yang akan kelak di lakukan terhadap hartanya setelah ia meninggal dunia kelak”. Pelaksanaan wasiat ini baru akan dilakukan setelah pewaris meninggal dunia.Kata kunci : wasiat, testamen